INFLUENCE OF FAMILIAL SOCIO-ECONOMIC RISK FACTORS ON INTELLECTUAL DISABILITY IN TIRUNELVELI DISTRICT, TAMIL NADU, INDIA - REVATHY, K. SOFIA; PRABA, L. JEYA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2022)
Intellectual disability is characterized as a “limitation both in intellectual functioning and adaptive behaviour as expressed in conception, social, and practical adaptive skills”. Various causal factors can be identified empirically as risk factors among families with intellectual disability. Though the genetic etiology contributes to 30-50% of intellectual disability, the contribution of environmental and socio-economic factors toward the etiology is also significant. Male gender, parental education, family income, and occupational status were the socio-economic risk factors that influence the etiology of Intellectual disability. Therefore, this descriptive cross-sectional study aims to look for the above said socio-economic risk factors among families with intellectual disability. A total of 203 families with one or more children with intellectual disabilities participated in the study. The participants were mothers of intellectually disabled children/individuals selected through special schools in the Tirunelveli District. The study results showed that the frequency of males affected was twice that of females affected. Fathers and mothers were of almost equal education status with 48.28% and 45.32% respectively in secondary school (standard 6th to 10th) educational range. Only 7.88% of mothers and almost 12% of the fathers had completed their higher secondary school education. Almost 12% of both parents have no education at all. Only 5% of fathers and 4% of mothers were undergraduates. Among the participants 42% work for daily wages and almost 36% work in unorganized private sectors. Only one parent is employed in 65% of the households and both were employed in 34% of the families. A total of 65.5% of families earn below 10,000 rupees per month. Thus, the identified socio-economic risk factors among families with intellectual disabilities can be used to scrutinize the population for primary prevention strategies and these risk factors can be evaded with proper awareness, education, and counselling.